Greenhouse gas fluxes over managed grasslands in Central Europe - Hörtnagl, L.; Barthel, M.; Buchmann, Nina; Eugster, W.; Butterbach-Bahl, Klaus; Díaz Pinés, Eugenio; Zeeman, M.; Klumpp, K.; Kiese, Ralf; Bahn, M.; Hammerle, A.; Lu, H.; et al. (Wiley, 2018)
Central European grasslands are characterized by a wide range of different management practices in close geographical proximity. Site‐specific management strategies strongly affect the biosphere–atmosphere exchange of the three greenhouse gases (GHG) carbon dioxide (CO2), nitrous oxide (N2O), and methane (CH4). The evaluation of environmental impacts at site level is challenging, because most in situ measurements focus on the quantification of CO2 exchange, while long‐term N2O and CH4 flux measurements at ecosystem scale remain scarce. Here, we synthesized ecosystem CO2, N2O, and CH4 fluxes from 14 managed grassland sites, quantified by eddy covariance or chamber techniques. We found that grasslands were on average a CO2 sink (−1,783 to −91 g CO2 m−2 year−1), but a N2O source (18–638 g CO2‐eq. m−2 year−1), and either a CH4 sink or source (−9 to 488 g CO2‐eq. m−2 year−1). The net GHG balance (NGB) of nine sites where measurements of all three GHGs were available was found between −2,761 and −58 g CO2‐eq. m−2 year−1, with N2O and CH4 emissions offsetting concurrent CO2 uptake by on average 21 ± 6% across sites. The only positive NGB was found for one site during a restoration year with ploughing. The predictive power of soil parameters for N2O and CH4 fluxes was generally low and varied considerably within years. However, after site‐specific data normalization, we identified environmental conditions that indicated enhanced GHG source/sink activity (“sweet spots”) and gave a good prediction of normalized overall fluxes across sites. The application of animal slurry to grasslands increased N2O and CH4 emissions. The N2O‐N emission factor across sites was 1.8 ± 0.5%, but varied considerably at site level among the years (0.1%–8.6%). Although grassland management led to increased N2O and CH4 emissions, the CO2 sink strength was generally the most dominant component of the annual GHG budget.